Vocabulary learning strategies preferences among the post-UPSR learners in Kota Kinabalu, Sabah - Dg Nursazwani Daud; Wardatul Akmam Din; Noraini Said; Suyansah Swanto (Global Academic Excellence (M) Sdn Bhd, 2022)
This study aimed to identify the extent to which vocabulary learning strategies influence the results of English writing in UPSR of the post-UPSR learners. The subjects were 267 high-achievers Form 1 learners from four secondary schools who had completed the UPSR in Kota Kinabalu, Sabah. The purpose of this study was to determine which VLSs was used the most frequently by the post-UPSR learners. Participants completed a VLS questionnaire and the findings revealed the strategies of vocabulary learning the post-UPSR inclined to employ from each category of determination, social, memory, cognitive, and metacognitive. We conclude that while VLSs use should be encouraged in general, instructors may not need to cater to individual vocabulary learning styles.